THE NUMERICAL SOLUTION OF THE HEAT DIFFUSION EQUATION VIA LATTICE BOLTZMANN METHOD - Atia, A; Mohammedi, k (University of Eloued جامعة الوادي, 2013)
In the present work, the solution of the heat diffusion problem is presented using lattice Boltzmann method (LBM). Thetwo dimensional task is considered and the different boundary conditions, specifically the Dirichlet and Neumann are taken into account. The D2Q4 lattice model is applied, To check the accuracy of the LBM algorithm,the same problems have been solved using the explicit variant of the finite difference method, In the final of the paper, the results of computations are shown and the conclusions are formulated.
1Eres journées internationales physique 16-17 Novembre 2013 Univercité Constantune 1
Keywords: Lattice Boltzùann method, numerical solution, diffusion equation